Leaving Their Drugs at the Gate? Exploring Changes in Drug Use From Before to During Incarceration in Norway - Andersen, Synøve N. (International journal of offender therapy and comparative criminology, 2025)
As the number of incarcerated persons who use drugs increases in many countries, it is important to understand the nature of drug use in prison by exploring how substance use patterns change from before to during incarceration. In this study, we rely on cross-sectional, self-report data from The Norwegian Offender Mental Health and Addiction (NorMA) study to identify the nature of changes in drug use among incarcerated respondents who reported having used either narcotics, non-prescribed medications, or both, during the 6 months before their incarceration (n = 824). Results show that about 60% (n = 490) stop using drugs. Of the remaining 40% (n = 324), about 86% changed their use patterns. Most commonly, incarcerated people stopped using stimulants and started using opioids; switching from cannabis to stimulants was the least common change. Overall, the study illustrates that the prison context leads most individuals to change their use patterns, some in unanticipated ways.